Knowledge and legitimacy: the fragility of digital mobilisation in Sudan. - Lamoureaux, Siri; Sureau, Timm (Journal of Eastern African Studies, 2019)
This paper examines digital mobilisation with respect to knowledge production, legitimacy and power in Sudan since new communication and surveillance technologies became widespread. Enthusiasm for digital opposition peaked with the Arab Spring and troughed through the repressive government apparatus. Social media (SMS, Facebook, Twitter) and crowdsourcing technologies can threaten the government's control over the public sphere as participatory practices. To arrive at this finding, we argue the significance of epistemological tools of those who control the representation of digital power, and approach state legitimacy as an ongoing and fragile process of constructing "reality" that requires continuous work to stabilise and uphold. At the same time, the paper describes an international counterpublic of security researchers and hackers who revealed that the Sudanese government invested greatly in controlling the digital landscape. We analyse Nafeer, a local grass-roots initiative for flood-disaster-relief that made use of digital media despite the digital suppression. Nafeer's challenge to the state came from the way it threatened the state-monopoly over knowledge, revealing both the fragility and the power of state legitimacy.